WHAT DRIVES INVESTMENT DECISIONS? EXAMINING THE ROLES OF DIGITAL FINANCIAL LITERACY, COGNITIVE ABILITY, AND RISK TOLERANCE THROUGH INTENTION TO INVEST - Reza Dwi Fauzhi; Maulida Nurul Innayah; Herni Justiana Astuti; Purnadi Purnadi (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Investment decision-making has become increasingly important as participation in digital investment platforms continues to grow. This study aims to examine the influence of digital financial literacy, cognitive ability, and risk tolerance on investment decisions, with intention to invest as a mediating variable. Drawing on the Theory of Planned Behavior (TPB) and Prospect Theory, this study employed a quantitative research design using a cross-sectional survey. Data were collected from 151 respondents through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that digital financial literacy and cognitive ability have positive and significant effects on investment decisions, whereas risk tolerance has no significant effect on investment decision. Intention to invest also has a positive and significant effect on investment decisions. Similarly, intention to invest mediated the relationship between digital financial literacy and cognitive ability on investment decisions, but does not to mediate the relationship between risk tolerance and investment decisions. By integrating digital financial literacy, cognitive ability, and risk tolerance within the TPB and Prospect Theory framework, this study provides a better understanding of investment decision-making among regional investors. The findings also offer practical implications for policymakers, financial educators, and financial institutions in designing programs to improve the quality of individual investment decisions.